Magnetic Resonance Imaging Availability Reduces Computed Tomography Use for Pediatric Appendicitis Diagnosis. Issue 1 (January 2022) - James, Natasha C.; Ahmadian, Rosstin; Mckee, Jason Q.; Sarangarm, Dusadee; Bussmann, Silas C.; Williamson, Susan; Upham, Bryan D.
Abstract : Objectives: To determine if introducing magnetic resonance imaging (MRI) as an imaging option for children with suspected appendicitis and an inconclusive ultrasound reduces computed tomography (CT) use. Methods: This is a retrospective cohort study of patients aged 5 to 18 years who presented to a pediatric emergency department (ED) with suspected appendicitis. Rates of CT use 1 year before and 1 year after MRI availability are compared. Secondary outcomes include missed and negative appendectomies, imaging charges, time to antibiotics and surgery, time to radiology read, ED length of stay, and test characteristics of MRI and CT. Results: Of the 981 patients screened, 499 patients met inclusion criteria. There was an absolute reduction of CT use of 25% from 38% in year 1 to 13% in year 2 (95% confidence interval, 18% to 33%). Advanced imaging charges were 371 higher in year 2 (MRI) than year 1 (CT), and median time to radiologist reads was longer in MRIs than CTs (129 versus 62 minutes; difference 53 minutes, 95% confidence interval, 23 to 74 minutes). All other secondary outcomes, including ED length of stay and test characteristics, were statistically similar. Conclusions: Introducing MRI for as an imaging option for children with suspected appendicitis and an inconclusive ultrasound markedly reduced CT use, but did result in a small increase in imaging charges and time to preliminary radiology read.